Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.24251/hicss.2022.726
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Media Bias, Social Identity Threat, and Conspiracy Theory Ideation During the COVID-19 Pandemic

Abstract: Social media organizations have an obligation to filter and sometimes exclude content, often based on machine learning algorithms. This has resulted in perceptions of bias in social media. When individuals perceive that a social media system is designed to exclude their point of view, they may experience a loss of self-worth, based on their excluded point of view. As a result, they may resist and avoid the technology that seems biased against them to prevent further loss of selfworth. They might also believe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…The original CMS validation study demonstrated that the conspiracy theory ideation subscale is suitable for measuring conspiracy beliefs in the US, New Zealand and Mace donia, and the subscale has been used widely for this purpose (e.g., Craig & Sadovykh, 2022;Gligorić et al, 2021). The skepticism subscale, on the other hand, has predicted belief in more mundane allegations, such as bribery and corruption, and the developers recommended its use when researchers want to partial out the variance caused by such a mundane suspiciousness from the suspicion that characterizes conspiracy beliefs.…”
mentioning
confidence: 99%
“…The original CMS validation study demonstrated that the conspiracy theory ideation subscale is suitable for measuring conspiracy beliefs in the US, New Zealand and Mace donia, and the subscale has been used widely for this purpose (e.g., Craig & Sadovykh, 2022;Gligorić et al, 2021). The skepticism subscale, on the other hand, has predicted belief in more mundane allegations, such as bribery and corruption, and the developers recommended its use when researchers want to partial out the variance caused by such a mundane suspiciousness from the suspicion that characterizes conspiracy beliefs.…”
mentioning
confidence: 99%